(untitled) (Baltic Journal of Sport and Health Sciences, 2012)
Research background and hypothesis. There are many obstacles for creativity in physical education teachers’ work but majority of physical education teachers tend to work creatively so it is worthwhile to explore which variables predict creativity. The hypothesis of the study: Personal factors are more important for physical education teachers’ creativity in comparison to social factors. Research aim was to identify individual and social factors, predicting creativity in the sample of physical education teachers. Research methods. Quantitative study. The questionnaire survey was used to establish the level of creativity, creative self-efficacy, motivation, emotions and the microclimate characteristics. The sample involved 120 physical education teachers. Research results. Creativity was predicted by self-efficacy and intrinsic process motivation. Extrinsic motivation inhibited creativity in physical education teachers’ work. Supervisory encouragement for creativity has the only social factor facilitating creativity. Discussion and conclusions. The obtained data confirmed interrelation between creativity and self-efficacy and validated results obtained by D. F. De Moulin (1993). Intrinsic process motivation also predicts creativity. It is in agreement with Y. Ommundsen and S. Eikanger Kvalo’s (2007) results. Extrinsic motivation has negative impact towards creativity. It is possible that teachers motivated intrinsically create task-involving motivational climate which leads to competitiveness (Ommundsen, Eikanger Kvalo, 2007). Supervisory encouragement is the only social variable predicting teachers’ creativity. The data revealed that supervisors’ behavior was more important than that of colleagues (Laker et al., 2008; Blankenship, Coleman, 2009). Keywords: creativity, personal and social factors.